Coexisting anatomical variation of the lateral femoral cutaneous nerve and genitofemoral nerve: A case report - Robert Haładaj; Ivan Varga (Elsevier, 2024)
Introduction: Anatomical variations of the nerves derived from the lumbar plexus are common and clinically valid. Therefore, this report aims to present the coexisting anatomical variations of the lateral femoral cutaneous and genitofemoral nerves. Case description: During routine dissection of an isolated male left lower limb (fixed in 10 % formalin solution), atypical arrangements of the lateral femoral cutaneous and genitofemoral nerves were found. The lateral femoral cutaneous nerve division level into anterior and posterior branches was high, above the inguinal ligament. Both branches passed beneath the inguinal ligament at the midpoint of the distance between the anterior superior iliac spine and the femoral artery. The anterior branch of the lateral femoral cutaneous nerve was better developed and had a greater diameter than the posterior branch. The femoral branch of the genitofemoral nerve was absent and partially replaced by the most medial branch derived from the anterior division of the lateral femoral cutaneous nerve. Conclusions: The lateral femoral cutaneous and genitofemoral nerves can show anatomic variability, which should be remembered during clinical assessments of nerve lesions and while performing surgical interventions.